INFLUENCE OF INTERACTIVE MULTIMEDIA LEARNING TO NURSING UNDERGRADUATE STUDENTS’ KNOWLEDGE GAIN AND RETENTION ABOUT MENTAL STATUS EXAMINATION - Djoko Priyono; Faisal Kholid Fahdi (Journal of Nursing Science Update (JNSU), 2019)
Mental status examination is a significant phase in delivering nursing care as the basis to make diagnosis. In the reality, a lot of nursing students still difficult to understand terminologies and structures in mental status assessment. Studies show that interactive multimedia may help students to understand real conditions of the patients which are difficult to visualized. However, in the context of mental status assessment, further research required. The design of the study is quasi experimental including pre and post test with control group. The knowledge score measured using instrument 40 items multiple choice self-developed based on theory and has been content and construct validity with Cronbach’s Alpha 0,94. The result was analyzed by using Mann-Whitney test showed that there was a significant difference mean score of intervention group (65,52 + 6,958) compared with control group (47,22 + 3,773) (p = 0,000). Knowledge retention of intervention group (62,13+6,681) and control group (42,45+3,232).The results of this study indicate there is a significant influence of interactive multimedia learning to improve undergraduate nursing students’ knowledge about mental status examination. It is advisable to Nurse Educator for using interactive multimedia to overcome the difficulties of the students in understanding the concepts of mental status examination.